Contratações públicas de inovação: uma análise dos estados brasileiros - Sousa, Izabel Sabino de (2023)
Public procurements represent a crucial instrument for fostering innovation and technological development. The increasing interest in using public contracts as a tool for innovation policy has drawn the attention of numerous researchers, both in Brazil and abroad. However, in the context of Brazilian states, there is still a significant gap in empirical studies regarding the effective utilization of these contracts. Given this knowledge gap, the research problem guiding this study is: 'How are state governments utilizing public procurements for innovation?' Thus, the general objective is to analyze the landscape of innovation-related public procurements in Brazilian state governments. To achieve this objective, the following specific objectives were delineated: to analyze the legal framework surrounding innovation-related public procurements at the state level in Brazil; to analyze innovation-related public procurements in state governments, and finally, to explore the facilitators and inhibitors of innovation-related public procurements. By examining legislation, and contracts, and conducting semi-structured interviews, this research gained a comprehensive understanding of the state-level landscape of innovation-related public procurements and identified the key factors associated with their implementation. At the conclusion of this analysis, it can be concluded that the use of these contracts is in its early stages, especially due to the low number of identified contracts. Despite positive perceptions regarding the promotion of innovation in public procurement and the efforts made thus far, there are still challenges to be overcome, such as fostering a culture of innovation, training public agents, and fostering closer collaboration between managers and oversight agencies.